Teaching and Learning Challenges On Implementation of Learner-Centred Pedagogy for English Language Subject in Selected Secondary Schools in Longido District - Olokwani, Naishiye Raphael; Mandila, Timoth; Semali, Ladislaus M. (international journal of Education, Learning and Development, 2022)
This paper explores the need of a good knowledge of the English language subject for teaching and learning processes. Tanzanian government is in a race to provide the quality education to all people. The study adopted mixed methods research under concurrent triangulation design. The theory guided this study was Social Constructivism. The target population for this study was 1381 respondents from Longido District. A sample of 100 respondents was selected through probability and non-probability methods. Questionnaires were used to collect quantitative data from secondary school teachers and students whereas interview guides were used to collect qualitative data from school heads and heads of English department. Validity was established through expert to the area of study whereas reliability was determined using split-half method. Credibility of qualitative data was ascertained by involving multiple analyses, whereas dependability was established through detailed reporting of the research process. Qualitative data were analyzed thematically along the research question and presented in narrative forms whereas quantitative data were analyzed using descriptive statistics and inferentially using ANOVA and presented in tables. The study concludes that LCP challenges can be diminished if seminars, workshops and enough resources can be offered to both teachers and students. The study recommends that school management and Ministry of Education Science and technology should motivate teachers by providing incentives, instructional resources and physical facilities when implementing LCP. Also teachers need to develop positive self-esteem, attitude and positive perception towards oneself. KEYWORDS: learner centred pedagogy, English